The Influence of Green Marketing Mix Strategy on Marketing Performance in Indonesian Food and Beverage SMEs - Daniels Marshall Aththarsyach; Totok Haryanto; Erny Rachmawati; Hengky Widhiandono (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
The implementation of sustainable marketing strategies has become a crucial issue for MSMEs in the food and beverage sector as environmental sustainability and business competitiveness are increasingly being addressed. This study aims to analyze the influence of the Green Marketing Mix (7P) on the marketing performance of MSMEs in Indonesia from a Resource-Based View (RBV) perspective. The study employed a quantitative method through a survey of 136 MSMEs selected using a convenience sampling technique. Data were collected using a Likert-scale questionnaire, then analyzed using Structural Equation Modeling–Partial Least Squares SEM-PLS using SmartPLS. The results showed that green people, green processes, and green physical evidence had a positive and significant effect on marketing performance, while green products, green prices, green places, and green promotions did not show a significant direct effect. These findings indicate that MSMEs' internal operational capabilities based on human resources, processes, and environmentally friendly physical evidence, are more effective in improving marketing performance than other strategic elements. This research provides theoretical contributions in the development of RBV-based green marketing studies as well as practical implications for MSMEs and policymakers in designing sustainable marketing strategies oriented towards strengthening internal capabilities.